EKSPLORASI ETNOMATEMATIKA KAIN TENUN SONGKET SUKU MELAYU SAMBAS - Sintong Panjaitan; Agung Hartoyo; Dona Fitriawan (Jurnal AlphaEuclidEdu, 2021)
This study aims to determine the mathematical concepts contained in forming the motifs of the Sambas Malay Tribe songket cloth and to describe the Sambas Malay Tribe songket woven cloth. This research is a qualitative research with an ethnographic approach. Subjects in this study were songket woven cloth craftsmen in the village of Sumber harapan Semberang hamlet, Sambas Regency, West Kalimantan with three speakers selected through Porpose Sampling, data collection techniques by interview, obsevation and dokumentation then analyzed, using data presentation and withdrawal. Conclusion. The results showed that : 1). The mathematical concepts contained in the manufacturing process of the Sambas Malay Tribe songket are counting, measuring, designing, locating and explaining; 2). The various motifs available from the songket woven cloth are shoots of bamboo shoots, chained clouds, betel trails, crowned peacock’s crest, grapes, orchids, eastern, stars, crowns, grass flowers and a single rose. Then identified mathematical concepts as concepts of flat plane geoemetry, such as straight lines, parallel lines, folding symmetry, rhombus, congruence, triangles and kites.